2009
DOI: 10.1080/07418820801989734
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Continuity of Sex Offending: Evidence from the Second Philadelphia Birth Cohort

Abstract: This study uses data from the Second Philadelphia Birth Cohort to examine the natural history of sex offenders and their involvement in sexual offending through age 26. Several key findings emerged from our effort. First, only one in 10 of the 221 mate and female juvenile sex offenders had a sex-related offense during the first eight years of adulthood. Second, 92 percent of all the cohort mates with adult sex records had no prior juvenile sex offense. Third, a boy with no sex contacts but five or more total j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
79
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 39 publications
11
79
2
1
Order By: Relevance
“…Its course reflects the variation that exists among the criminal population in terms of offending rate or frequency-oftentimes denoted by the Greek lambda (λ) (Blumstein, Cohen, Piquero, & Visher, 2010;Brame, Paternoster, & Bushway, 2004;Francis et al, 2004;Hochstetler, DeLisi, & Puhrmann, 2007;Lattimore et al, 2004;Miles & Ludwig, 2007;Monahan & Piquero, 2009;Odgers et al, 2008;Paternoster, Brame, & Farrington, 2001;Piquero, 2000a;Pollock, Joo, & Lawton, 2010;Ramoutar & Farrington, 2006), persistence/continuity (Blokland, Nagin, & Nieuwbeerta, 2005;Brame, Bushway, Paternoster, & Thornberry, 2005;Ewart, Oatley, & Burn, 2005;Ge, Donnellan, & Wenk, 2001;Mazerolle et al, 2000;Zimring, Jennings, Piquero, & Hays, 2009), and career length or span (Francis, Soothill, & Piquero, 2007;Haapanen, Britton, & Croisdale, 2007;Kazemian & Farrington, 2006;Kazemian, Le Blanc, Farrington, & Pease, 2007;Piquero, Brame, & Lynam, 2004;Piquero & Buka, 2002). Whereas most offending careers are brief, truncated, and intermittent (Piquero, 2004), some are prolonged and essentially life-long.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Its course reflects the variation that exists among the criminal population in terms of offending rate or frequency-oftentimes denoted by the Greek lambda (λ) (Blumstein, Cohen, Piquero, & Visher, 2010;Brame, Paternoster, & Bushway, 2004;Francis et al, 2004;Hochstetler, DeLisi, & Puhrmann, 2007;Lattimore et al, 2004;Miles & Ludwig, 2007;Monahan & Piquero, 2009;Odgers et al, 2008;Paternoster, Brame, & Farrington, 2001;Piquero, 2000a;Pollock, Joo, & Lawton, 2010;Ramoutar & Farrington, 2006), persistence/continuity (Blokland, Nagin, & Nieuwbeerta, 2005;Brame, Bushway, Paternoster, & Thornberry, 2005;Ewart, Oatley, & Burn, 2005;Ge, Donnellan, & Wenk, 2001;Mazerolle et al, 2000;Zimring, Jennings, Piquero, & Hays, 2009), and career length or span (Francis, Soothill, & Piquero, 2007;Haapanen, Britton, & Croisdale, 2007;Kazemian & Farrington, 2006;Kazemian, Le Blanc, Farrington, & Pease, 2007;Piquero, Brame, & Lynam, 2004;Piquero & Buka, 2002). Whereas most offending careers are brief, truncated, and intermittent (Piquero, 2004), some are prolonged and essentially life-long.…”
Section: Introductionmentioning
confidence: 97%
“…Beginning with the seminal Philadelphia Birth Cohort Studies (Wolfgang et al, 1972;Tracy et al, 1990), the two-volume study by Zimring, Jennings, Piquero, & Hays, 2009), and even police officers (Harris, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Whereas several studies have found a relation between a history of nonsexual offenses and sexual recidivism (Allan, Allan, Marshall, & Kraszlan, 2003;Caldwell, 2007;McCann & Lussier, 2008;Nisbet et al, 2004), and others have found a relation between sexual recidivism and a history of impulsivity, psychopathy, antisocial personality characteristics, and truancy (Caldwell et al, 2008;Gretton, McBride, Hare, O'Shaughnessy, & Kumka, 2001;Schram, Milloy, & Rowe, 1991;Worling, 2001), a number of studies (Kahn & Chambers, 1991;Lab, Shields, & Schondel, 1993;Långströ m, 2002;Rasmussen, 1999;Sipe et al, 1998;Worling & Curwen, 2000) have failed to find a relation between nonsexual offending and sexual recidivism. Nonetheless, some evidence suggests that antisociality may play a role in predicting persistence of sexually coercive behavior into adulthood (Parks & Bard, 2006;Zimring et al, 2009Zimring et al, , 2007. Consistent with the pattern of these results, Worling and Långströ m (2006) have listed antisocial interpersonal orientation and impulsivity as only possible risk factors for sexual recidivism.…”
Section: Antisocial Behavior and Impulsivitymentioning
confidence: 59%
“…In more recent meta-analyses of predictive factors for JSOs (Hanson & Morton-Bourgon, 2004;McCann & Lussier, 2008) and reviews of sexual recidivism (Worling & Långström, 2006), sexualization as indexed by previous sexual charges/convictions and deviant sexual interests has been shown to have moderate predictive potency, but the efficacy of this component in predicting persistence into adulthood has had mixed support (e.g., Parks & Bard, 2006;Rubinstein et al, 1993;Sample & Bray, 2003;Zimring et al, 2009Zimring et al, , 2007. Moreover, the specific measure of this sexualization component in the JSOAP-II Factor 1 has yielded mixed results (e.g., Prentky, 2006;Viljoen et al, 2008).…”
Section: Hypersexuality and Sexual Deviancementioning
confidence: 96%
See 1 more Smart Citation